Maintaining women’s integrity during childbirth through participatory action research - Muda, Siti Mariam; Fahy, K.; Hastie, C. (2013)
Pelvic floor trauma following childbirth has negative effects on women physically and physiologically. The aim of the study is to improve midwifery practice, so as to optimise birth outcomes and minimise pelvic floor trauma for birthing women. Participatory action research was undertaken at Kuala Lumpur Maternity Hospital by the means of semi-structured interview (senior midwife and obstetrician doctors), focus groups (nurse manager and clinical nurse midwife), direct observation and reflective journals. Data were then analysed using content analysis, thematic analysis and reflection. At the same time, strengthening the qualitative outcomes, a self-administered questionnaire was distributed to nurse-midwife and analysed using the SPSS. The finding revealed that there are several strategies can reduce the rates of pelvic floor trauma: better staff training on evidence-based practiced, the development and implementation new clinical guidelines for midwifery practice in labour ward, coupled with strong internal support. Extensive staff training was planned, and new midwifery practice guidelines were drafted by the researchers in consultation with senior midwives. Change to midwifery practice in labour ward is possible if there is support from key players in the organisations, staff training is extensive and nurse-midwives are supported by evidence-based guidelines. Keywords: Pelvic floor / perineal /pelvic floor trauma, childbirth, risk factors